2010
DOI: 10.1186/1471-2229-10-183
|View full text |Cite
|
Sign up to set email alerts
|

Medicago truncatula contains a second gene encoding a plastid located glutamine synthetase exclusively expressed in developing seeds

Abstract: Background Nitrogen is a crucial nutrient that is both essential and rate limiting for plant growth and seed production. Glutamine synthetase (GS), occupies a central position in nitrogen assimilation and recycling, justifying the extensive number of studies that have been dedicated to this enzyme from several plant sources. All plants species studied to date have been reported as containing a single, nuclear gene encoding a plastid located GS isoenzyme per haploid genome. This study reports the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…In L. japonicus , a closely related model legume, single GS2 and GS1 isoforms were detected with an in‐gel activity assay, as well as one hmGS protein in Western blots of native PAGE gels, which represented a dissociated GS2 tetramer with no activity (Betti et al , ). Generally, a small gene family (from two to four functional GLN1 genes) encoding for different cytosolic (GS1) isoforms and a single gene encoding for GS2 ( GLN2 ) are mostly present in plants (Betti et al , ), although it was recently shown that Medicago truncatula contains two functional GS2 genes (Seabra et al , ). Cytosolic isoforms are expressed in different plant organs, with specific roles in primary N assimilation in the root, N remobilization during senescence, N translocation in the vasculature (reviewed by Bernard & Habash, ).…”
Section: Discussionmentioning
confidence: 99%
“…In L. japonicus , a closely related model legume, single GS2 and GS1 isoforms were detected with an in‐gel activity assay, as well as one hmGS protein in Western blots of native PAGE gels, which represented a dissociated GS2 tetramer with no activity (Betti et al , ). Generally, a small gene family (from two to four functional GLN1 genes) encoding for different cytosolic (GS1) isoforms and a single gene encoding for GS2 ( GLN2 ) are mostly present in plants (Betti et al , ), although it was recently shown that Medicago truncatula contains two functional GS2 genes (Seabra et al , ). Cytosolic isoforms are expressed in different plant organs, with specific roles in primary N assimilation in the root, N remobilization during senescence, N translocation in the vasculature (reviewed by Bernard & Habash, ).…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms include a cytosolic form, GS1, and a chloroplastic form, GS2 (Bielawski 1993;Miflin and Habash 2002). In general, there is only one gene encoding GS2, with the exception of Medicago truncatula for which two genes were cloned (Seabra et al 2010); however, a small, multi-gene family encodes for the GS1 proteins (Masclaux-Daubresse et al 2010). At this time, at least three GS1 genes in rice (Tabuchi et al 2005), five genes in maize (Martin et al 2006) and seven genes in wheat (Bernard et al 2008) have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine synthetase (GS) is involved in the reassimilation of ammonium released by many processes such as deamination of amino acids, protein catabolism, and photorespiration (Seabra et al, 2010). During plant growth and development, nitrogen can be assimilated with the action of glutamine synthetase, forming glutamine.…”
Section: Enzymes Activitymentioning
confidence: 99%
“…Glutamine synthetase has two isoforms: a cytosolic GS1, which is involved in nitrogen remobilization, and a chloroplastic GS2, which is involved in nitrogen assimilation (Pegeau et al, 2006). GS is involved in the reassimilation of ammonium released by a number of biochemical processes such as protein catabolism, deamination of amino acids, and photorespiration (Seabra et al, 2010). The effects of SA and FB1 on glutamine synthetase activity have been studied in Roblin and Frontana.…”
Section: Glutamine Synthetasementioning
confidence: 99%
See 1 more Smart Citation